Religious Belief on Online Buying Intention of Muslim Clothing in Indonesia - Aprianto, Ronal; Salim, Muhartini; Sardiyo, Sardiyo (International Review of Management and Marketing, 2021)
The purpose of this study is to determine the influence of religious belief on the online buying intention of Muslim clothing in Indonesia. The data in this study were obtained from questionnaires distributed to 762 respondents. This study uses quantitative research by distributing questionnaires using online forms through Zoho. The unit of analysis of this study is all generations (Baby Boomers, Generation X (Gen X or Xers), and Millennials) who have shopped for online Muslim clothing in Indonesia. The method used in sampling is purposive sampling aimed at all respondents who have shopped online. The method is through Lisrel 8.7 program and t-test. These results indicate that religious belief influences the online buying intention of Muslim clothing in Indonesia. Keywords: Religious Belief, Online Buying Intention, Indonesia JEL Classifications: MO, M31, Z12 DOI: https://doi.org/10.32479/irmm.11887